Single Unit Cell Bismuth Tungstate Layers Realizing Robust Solar CO2 Reduction to Methanol - Liang, Liang; Lei, Fengcai; Gao, Shan; Sun, Yongfu; Jiao, Xingchen; Wu, Ju; Qamar, Shaista; Xie, Yi (Angewandte Chemie International Edition, 2015)
Solar CO2 reduction into hydrocarbons helps to solve the global warming and energy crisis. However, conventional semiconductors usually suffer from low photoactivity and poor photostability. Here, atomically‐thin oxide‐based semiconductors are proposed as excellent platforms to overcome this drawback. As a prototype, single‐unit‐cell Bi2WO6 layers are first synthesized by virtue of a lamellar Bi‐oleate intermediate. The single‐unit‐cell thickness allows 3‐times larger CO2 adsorption capacity and higher photoabsorption than bulk Bi2WO6. Also, the increased conductivity, verified by density functional theory calculations and temperature‐dependent resistivities, favors fast carrier transport. The carrier lifetime increased from 14.7 to 83.2 ns, revealed by time‐resolved fluorescence spectroscopy, which accounts for the improved electron‐hole separation efficacy. As a result, the single‐unit‐cell Bi2WO6 layers achieve a methanol formation rate of 75 μmol g−1 h−1, 125‐times higher than that of bulk Bi2WO6. The catalytic activity of the single‐unit‐cell layers proceeds without deactivation even after 2 days. This work will shed light on designing efficient and robust photoreduction CO2 catalysts. Single unit cell Bi2WO6 layers (right) are synthesized by virtue of a lamellar Bi‐oleate intermediate (middle). Benefiting from the ultrahigh fraction of surface atoms and increased DOS, the single‐unit‐cell Bi2WO6 layers achieve a methanol formation rate of 75 μmol g−1 h−1, 125‐times higher than that of the bulk Bi2WO6 and also over 10‐times higher than that of previously reported TiO2‐loaded zeolite and Ag/TiO2.